How the employees' perceptions of corporate social responsibility make them happier and psychologically stronger - Leal, Susana (2016)
Corporate social responsibility (CSR) has been studied primarily at the macro level, with few studies taking into account the individual level. Furthermore, there are calls for more investigation on the antecedents of employees’ psychological capital (PsyCap). This study bolsters both areas. The paper shows how the employees’ perceptions of CSR predict their PsyCap both directly and through the mediating roles of positive affect and the sense of meaningful work. Two hundred and seventy-nine employees participate. The study uses structural equation modeling to test the hypothesized model. The findings suggest that both positive affect and the sense of meaningful work partially mediate the relationship between the perceptions of CSR and PsyCap. The study helps to understand the underlying mechanisms linking CSR with outcomes at the individual level. Studying CSR at the individual level is valuable for both academic and practical reasons.